A, Literature Literature Review Penggunaan Warehouse Management System (WMS) terhadap Akurasi Order Picking di Gudang - Shrimeta Oktavia Rhomazani; Silviah Silviah; Ondo Salverius Sipayung; Andreas Panjaitan (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
The objective of this research is to systematically explore the influence of the Warehouse Management System (WMS) on the accuracy of order picking within warehouses by utilizing a Systematic Literature Review (SLR) approach. A total of 24 research articles, both national and international, were examined using thematic synthesis and data. The results reveal that the adoption of WMS significantly boosts operational efficiency and improves accuracy in order picking by integrating technologies such as the Internet of Things (IoT), Radio Frequency Identification (RFID), and Artificial Intelligence (AI), which together are effective in lowering human error by as much as 98%. Nonetheless, the success of WMS implementation primarily relies on how prepared the organization is, the skills of its workforce, managerial backing, and having sufficient digital infrastructure. This review also points out an empirical gap in research within Indonesia, where many existing studies remain descriptive and have not yet quantified the direct correlation between WMS usage and warehouse accuracy performance. This study makes both theoretical and practical contributions to the advancement of competitive smart warehouse models and serves as a vital reference for upcoming research and the formulation of digital logistics policies.